Protective Effect of Moderate Exercise for BALB/c Mice with Salmonella Typhimurium Infection - Campos-Rodríguez, R.; Godínez-Victoria, M.; Arciniega-Martínez, I. M.; Reséndiz-Albor, A. A.; Reyna-Garfias, H.; Cruz-Hernández, T. R.; Drago-Serrano, M. E. (International Journal of Sports Medicine, 2016)
Moderate exercise enhances resistance to pathogen-associated infections. However, its influence on intestinal IgA levels and resistance to Salmonella typhimurium in mice has not been reported. The aim of this study was to assess the impact of moderate exercise on bacterial resistance and the intestinal-IgA response in a murine typhoid model. Sedentary and exercised (under a protocol of moderate swimming) BALB/c mice were orally infected with Salmonella typhimurium and sacrificed on days 7 or 14 post-infection (n=5 per group). Compared with infected sedentary mice, infected exercised animals had i) lower intestinal and systemic bacterial loads; ii) higher total and specific intestinal-IgA levels, iii) a higher percentage of IgA plasma cells in lamina propria; iv) a higher level on day 7 and lower level on day 14 of intestinal α- and J-chain mRNA and plasma corticosterone, v) unchanged mRNA expression of intestinal pIgR, and vi) a higher mRNA expression of liver pIgR, α-chain and J-chain on day 7. Hence, it is likely that an increase in corticosterone levels (stress response) induced by moderate exercise increased intestinal IgA levels by enabling greater liver expression of pIgR mRNA, leading to a rise in IgA transcytosis from the liver to intestine. The overall effect of these changes is an enhanced resistance to infection.
Keywords: immunoglobulin A; murine typhoid infection; training; stress; corticosterone